Lesson Study Dalam Peningkatan Kualitas Pembelajaran di Madrasah Ibtidaiyah Maâarif Kejiwan Wonosobo - Muntaqo, Rifqi; Masruroh, Dwi (BELAJEA: Jurnal Pendidikan Islam, 2016)
This research analyzes the lesson study learning model implemented in MI Maarif Kejiwan Wonosobo an effort to improve the quality of learning and student achievement. This research aims to determine aspects of school management that occurred in MI Maarif Kejiwan Wonosobo in the implementation of lesson study. This research is a qualitative field research, data collection techniques as for the emphasis on participant observation, interview and documentation. Data analysis techniques used by Miles and Huberman, analysis consists of three activities, namely the flow of data reduction, data presentation, and conclusion or verification. This research is a case study because the focus of this research is to answer the question "how" the concept of improving the quality of learning through lesson study and implementation in improving the quality of learning and analyzing support factors and obstacles in the implementation process of lesson study in MI Maarif Kejiwan. Keywords: Learning model, Lesson Study, and Learning Quality